Analysis of flexural and shear resistance of ultra high performance fiber reinforced concrete beams without stirrups. (1st November 2018) - Kodur, Venkatesh; Solhmirzaei, Roya; Agrawal, Ankit; Aziz, Esam M; Soroushian, Parviz
Highlights: Comparative behavior of UHPFRC beams under flexural and shear loading is presented. Effectiveness of fibers in enhancing shear capacity of UHPFRC beams is investigated. Feasibility of removing stirrups in UHPFRC beams is explored. Abstract: This paper analyzes failure characteristics of Ultra High Performance Fiber Reinforced Concrete (UHPFRC) beams under flexural and shear loading. Four large scale beams, fabricated with a specially designed mix comprising of coarse aggregate, were tested to trace structural behavior of UHPFRC members. The beams had relatively low tensile reinforcement ratio and no shear reinforcement to take advantage of high tensile and shear strength exhibited by UHPFRC. The test variables included longitudinal reinforcement ratio and type of loading (flexure and predominant shear). Two beams were tested under flexural loading while the other two beams were tested under dominant shear loading. Results from these tests indicate that UHPFRC beams exhibit a distinct cracking pattern characterized by formation of multiple microcracks at initial stages, followed by propagation of a singular macrocack at the critical section with increased loading. Further, comparative results indicate that absence of shear reinforcement in UHPFRC beams did not lead to any reduction in either ductility or moment capacity of the beams even under dominant shear loading.